Sensemaking, Sense-Censoring and Strategic Inaction: The Discursive Enactment of Power and Politics in a Multinational Corporation. Issue 9 (September 2016) - Whittle, Andrea; Mueller, Frank; Gilchrist, Alan; Lenney, Peter
In this paper we contribute to knowledge of power and politics in international business by developing the understanding of the role of discourse and sensemaking in the subsidiary–headquarters relationship. Based on an ethnographic action research study in a British subsidiary of an American multinational corporation, we conduct an ethnomethodologically informed discourse analysis of the accounts, stories and metaphors through which power and politics in the subsidiary–headquarters relationship were created as social facts. We then broaden the analytic frame to trace longitudinally how these facts led the subsidiary managers to hide, dilute or restrict their 'local sense' from the headquarters, including their knowledge of the local market and their preferred strategic direction for the firm: a process we term sense-censoring. We reveal how the subsidiary used power and politics as reasoning procedures to decide against pursuing a preferred course of action, despite a strongly held belief to the contrary, due to anticipated reactions or counter-actions, thereby transforming potential strategic action into inaction. Sense-censoring is significant for international business management, we propose, because it impacts upon knowledge flows, innovation diffusion and organizational learning. We conclude by outlining the implications of systems of sense-censoring and strategic inaction for the management of global–local relations in multinational corporations.